Perdagangan dan pertumbuhan di RCEP: Ekspor vs impor terhadap produk domestik bruto - Faisha Aprilia Riskiyah Aisyi; Windhu Putra (Journal of Economics Research and Policy Studies, 2025)
This study examines the effects of exports and imports on gross domestic product (GDP) in six member countries of the Regional Comprehensive Economic Partnership (RCEP) over 2013–2022. Using secondary data from the World Integrated Trade Solution (WITS), the analysis applies panel data regression to test the significance of trade variables for economic output. The results show that exports have a positive and statistically significant effect on GDP. This pattern is consistent with stronger global demand following the post-2008 recovery and the COVID-19 rebound, alongside a shift toward higher-value-added exports and improved export capacity, supported by strategic industrial policies and commodity downstreaming. In contrast, imports show a negative, though statistically insignificant, relationship with GDP. This weak import–GDP linkage is due to the dominance of consumer goods and processed oil and gas imports, limitations in domestic infrastructure and technological capacity, dependence on raw commodity exports, and the suboptimal orientation of trade policy.